2016
DOI: 10.1039/c6sm00767h
|View full text |Cite
|
Sign up to set email alerts
|

Collective and convective effects compete in patterns of dissolving surface droplets

Abstract: Detlef (2016) Collective and convective effects compete in patterns of dissolving surface droplets. Soft Matter, 12 (26 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
(25 reference statements)
3
40
0
Order By: Relevance
“…Therefore, it is not surprising that a number of groups has simulated evaporating fluids using the LBM recently. Ledesma-Aguilar et al [22,23] present a diffusion based evaporation method based on the free energy multiphase lattice Boltzmann method and demonstrate quantitative agreement with several benchmark cases as well as qualitative agreement with the experimental data of evaporating droplet arrays. Jansen et al [24] study the evaporation of droplets on a chemically patterned substrate and qualitatively compare the simulation results with experimental data.…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, it is not surprising that a number of groups has simulated evaporating fluids using the LBM recently. Ledesma-Aguilar et al [22,23] present a diffusion based evaporation method based on the free energy multiphase lattice Boltzmann method and demonstrate quantitative agreement with several benchmark cases as well as qualitative agreement with the experimental data of evaporating droplet arrays. Jansen et al [24] study the evaporation of droplets on a chemically patterned substrate and qualitatively compare the simulation results with experimental data.…”
Section: Introductionmentioning
confidence: 67%
“…Consequently, from Eqs. (23) and (20), our analysis yields the following law for the evaporation flux: where a 1 and a 2 are two constant numbers. By inspection of Eq.…”
Section: Evaporative Fluxmentioning
confidence: 95%
“…From the point of view of the governing equations, the evaporation of a liquid is similar to the dissolution of a liquid into another. Recent attention has been devoted to the sessile drop dissolution [21,22,23] and bubble growth in supersaturated solutions [24] with a combination of experimental, numerical and theoretical investigations. These studies show that natural convection is also observed above dissolving drops.…”
Section: Introductionmentioning
confidence: 99%
“…the effect of the neighbouring droplets). When there are multiple droplets, one expects that the presence of the neighbouring droplets leads to shielding effects, as are indeed seen in Carrier et al (2016), Laghezza et al (2016), Bao et al (2018) and Wray, Duffy & Wilson (2019). As a result, the lifetime for multiple droplets becomes longer than that for a single droplet.…”
Section: Introductionmentioning
confidence: 94%
“…These authors have constructed the theoretical framework to account for such purely diffusive shielding effects; but, for collective effects affected by convection, many questions remain open. Laghezza et al (2016) have experimentally studied collective droplet dissolution in the regime in which convection is relevant. They report that, remarkably, the neighbouring droplets can enhance the mass flux because of enhanced buoyancydriven convective flow in the bulk, but the detailed fluid dynamics of the process remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%